1999
DOI: 10.1016/s0378-7206(98)00086-x
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the IT satisfaction of small-business users

Abstract: Although there are many articles in the NIS literature which address small-business computing, in effect the organizations represented in these studies are, in many ways, similar to medium-and large-sized organizations. In this article, we focus on businesses that are truly small: they have very few employees and there is no formal NIS department. In this environment, the small business owner/manager is the principal user and has to perform most of the IT functions. For such an environment, an IT satisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
10

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 20 publications
4
52
0
10
Order By: Relevance
“…However, age has a negative influence (probably because age is negatively correlated with the ease of use), as show several research (Warr 1993;Ford et al 1996;Palvia and Palvia 1999;Chapman et al 2000;Borghans and Weel 2002;Rouvinen 2002;Aubert et al 2006;De Koning and Gelderblom 2006;Schleife 2006;Shih-Yung and Pearson 2011) due to the loss of cognitive technological skills and the increase of the resistance to change. Control variables are not relevant in the context of this analysis.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…However, age has a negative influence (probably because age is negatively correlated with the ease of use), as show several research (Warr 1993;Ford et al 1996;Palvia and Palvia 1999;Chapman et al 2000;Borghans and Weel 2002;Rouvinen 2002;Aubert et al 2006;De Koning and Gelderblom 2006;Schleife 2006;Shih-Yung and Pearson 2011) due to the loss of cognitive technological skills and the increase of the resistance to change. Control variables are not relevant in the context of this analysis.…”
Section: Resultsmentioning
confidence: 98%
“…Empirical research conducted by Palvia and Palvia (1999) and Chapman et al (2000), have found that the owner's age is a factor that can determine the successful adoption of ICT by small businesses (Ford et al 1996), as the ageing of employees or owners sometimes poses serious problems with regard to the adoption of ICT by businesses, particularly small ones. Several earlier studies have focused on the study of the moderating effect of age on technological change.…”
Section: The Age Of the Entrepreneur And The Use Of Ictmentioning
confidence: 99%
See 2 more Smart Citations
“…Selon les auteurs consultés, on peut retrouver plusieurs facteurs dans chacune des catégories présentées. La qualité des données, la sécurité des équipements, la formulation claire d'objectifs et leur promotion, la coopération entre les services, le soutien de la direction, la disponibilité des ressources, la présence d'un champion, la perception d'utilité, la participation et la satisfaction des utilisateurs, l'encouragement à l'utilisation, la tenue de réunions, la gestion des problèmes, la perception et l'historique de l'entreprise en matière de changement en sont des exemples (Igbaria, Parasuraman et Baroudi, 1996 ;Jacob, 2000 ;Korunka et Carayon, 1999 ;Palvia, 1996 ;Palvia et Palvia, 1999 ;Tang, 2000). Puisque ces facteurs contribuent à créer un environnement plus ou moins propice aux changements technologiques et que, par conséquent, ils risquent ultimement d'influencer l'appropriation technologique des individus, ils sont retenus aux fins de l'analyse qualitative à réaliser concernant le contexte organisationnel de la PME.…”
Section: La Nature Des Pme Et Les Facteurs Critiques De Succès De L'aunclassified